2018
DOI: 10.5530/ijper.52.4s.103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Comparative Immunomodulatory Potential of Solanum xanthocarpum Root and Fruits on Experimental Animal

Abstract: Aim: This study was aimed to justify the scientific basis in folklore use of Solanum xanthocarpum (solanaceae) as an Immunomodulatory agent in India. Materials and Methods: The ethanol and aqueous extracts of S. xanthocarpum fruit (SXE-1 and SXA-1), root (SXE-2 and SXA-2) and whole plant (SXE-3 and SXA-3) were evaluated for immunomodulatory activity by using cold water swim endurance stress test, delayed type hyper sensitivity reaction, carbon clearance test and CCl 4 induced oxidative stress model on experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…The immunomodulatory agents regulate the cytokine production such as, tumour necrosis factor, interleukin and interferon and these cytokines may, in turn activate T cells or NK cells. 24,25 IL-2 promotes growth and activation of T lymphocytes and natural killer (NK) cells. Tumour necrosis factor (TNF) α is an endogenous pyrogen, is responsible for apoptotic cell death to inhibit tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory agents regulate the cytokine production such as, tumour necrosis factor, interleukin and interferon and these cytokines may, in turn activate T cells or NK cells. 24,25 IL-2 promotes growth and activation of T lymphocytes and natural killer (NK) cells. Tumour necrosis factor (TNF) α is an endogenous pyrogen, is responsible for apoptotic cell death to inhibit tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pandey, ( 35) have been reported that the seed fumes of S. surattense were useful in the treatment of tooth pain and pain from gingival swellings. In India, Rajasthan Mukunda tribes traditionally use the root parts of S. surattense in the treatment of hernia (36). Alcoholic extracts of S. surattense leaf have significant antiulcer potentiality (37) than other solvent extracts.…”
Section: Pharmacologymentioning
confidence: 99%
“…Entire plant used for treating leprosy, dropsy, and cough by the folklore (Madhavi et al, 2014). Mukunda tribes of Rajasthan, India used the root paste for the treatment of hernia (Pandey et al, 2018). Root poultice used to treat the piles are practicing as a traditional medicine in many villages of South India.…”
Section: Ethno Medicinal Usagementioning
confidence: 99%
“…The Ayurvedic text mentioned that S. surattense possess anti piles activity (Pandey et al, 2018). Indian tribe to cure piles since from the ancient past has used a root of S. surattense, as a traditional medicine.…”
Section: Anti-piles Activitymentioning
confidence: 99%